Giosue Carducci — u źródeł ideologicznych włoskiego nacjonalizmu - Sondel-Cedarmas, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
The article is an analysis of political thought of Giosue Carducci 1835–1907, Italian poet and politician. It particularly deals with the role he played in the shaping of nationalist ideology in Italy. In his literary works and parliamentary speeches, Carducci – nicknamed “The Bard of New Italy,” supporter of monarchy and of the imperialistic policies of Francesco Crispi, enemy of clericalism – proclaimed a cult of ancient pagan Rome, of Risorgimento heroes and of Italy’s glory. Although Carducci cannot be recognized as a nationalist, it would be difficult to deny that at the beginning of the twentieth century his concepts became an inspiration for the architects of nationalist ideology in Italy E. Corradini, L. Federzoni, G.A. Borghese. The idea, promoted by Carducci, of the magnificence, grandeur and power of ancient Rome romanita which should be restored by Italian nation and his conviction that Italy ought to play an exceptional role in the European political system, were especially appealing to Italian nationalists. They shared the concept of strong and powerful Italy,respected by other nations. They held Prime Minister Francesco Crispi in a very high esteem and regarded him with huge sentiment he was supposed to be the only one who dared to implement these ideas. They also shared the antipathy towards parliamentary system, operation of political parties, liberal politicians Di Rudini, Giolitti and socialism which gradually increased its power. Carducci’s and nationalists’ critical attitude towards the actions of ruling class, which was unable to adjust its decisions to the lofty traditional ideals and towards parliamentarianism, was connected with the demand to strengthen monarchical system and to introduce “strong-arm rule” under the leadership of charismatic figure whose task was to solve the internal problems of the state and to execute the ambitious imperialistic policy.
Keywords: Carducci, Giosue (1835–1907); Włochy; ideologia; nacjonalizm